2014
DOI: 10.1186/1745-6150-9-10
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the orphan enzymes

Abstract: The emergence of Next Generation Sequencing generates an incredible amount of sequence and great potential for new enzyme discovery. Despite this huge amount of data and the profusion of bioinformatic methods for function prediction, a large part of known enzyme activities is still lacking an associated protein sequence. These particular activities are called “orphan enzymes”. The present review proposes an update of previous surveys on orphan enzymes by mining the current content of public databases. While th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 68 publications
0
43
0
Order By: Relevance
“…Information about these genes can be easily obtained from KEGG database using the identified KEGG-reaction number of the steps involved in a pathway ( Figure 7B). Notably, MEG6 includes 2 steps for which the KEGG reaction number is known, but the gene information is unknown because they are orphan enzymes (Shearer et al, 2014;Sorokina et al, 2014;Watschinger and Werner, 2013).…”
Section: Thermodynamic Feasibility Gene Availability and Pathway Yimentioning
confidence: 99%
See 1 more Smart Citation
“…Information about these genes can be easily obtained from KEGG database using the identified KEGG-reaction number of the steps involved in a pathway ( Figure 7B). Notably, MEG6 includes 2 steps for which the KEGG reaction number is known, but the gene information is unknown because they are orphan enzymes (Shearer et al, 2014;Sorokina et al, 2014;Watschinger and Werner, 2013).…”
Section: Thermodynamic Feasibility Gene Availability and Pathway Yimentioning
confidence: 99%
“…Both reactions/steps of the only 2-step long MEG-producing pathway ( Table S3 in the supplementary data) belonged to KEGG, but the 1 st reaction (R05351) is an orphan enzyme, i.e., the gene information for the reaction is unknown (Shearer et al, 2014;Sorokina et al, 2014;Watschinger and Werner, 2013). A closer look at the accepted 3 and 4-step pathways (Figure 3) revealed that at least one novel reaction existed in each pathway, while no pathway was found in which all reactions/steps were known to be biological ( Figures 3A and 3B), i.e., belonged to the KEGG database with a KEGG-reaction number.…”
Section: Enumeration Of the Acetyl-coa To Mono-ethylene Glycol (Meg)-mentioning
confidence: 99%
“…In addition, large-scale sequencing projects have revealed that 30-40% of the proteins encoded in prokaryotic genomes have no clearly known function, and the vast majority belong to thousands of unknown orthologue families that continue to grow as more genomes are sequenced [8]. On the other hand, it is also estimated that about 1,000 of the >5,500 enzymatic activities described by the International Union of Biochemistry and Molecular Biology in the EC classification system lack an associated nucleic or protein sequence in the public databanks, a situation known as the 'orphan enzyme problem' [9][10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…Focused analyses of new sequences for members of 37 protein families deposited in 2005 have shown that about 40% of these proteins remain misannotated (7,8). Our knowledge gap also includes over 1,000 of the known enzyme activities in the Enzyme Classification (of the 4,997 EC numbers) that have no associated gene sequence (orphan enzymes) (9,10).…”
mentioning
confidence: 99%